2017
DOI: 10.1371/journal.pone.0185641
|View full text |Cite
|
Sign up to set email alerts
|

‘Timed Up and Go’ test: Age, gender and cognitive impairment stratified normative values of older adults

Abstract: AimsThe aim of this study was to establish ‘Timed up and Go’ test (TUG) normative data among community dwelling older adults stratified based on cognitive status, gender and age groups.MethodsA total of 2084 community dwelling older adults from wave I and II were recruited through a multistage random sampling method. TUG was performed using the standard protocol and scores were then stratified based on with and without mild cognitive impairment (MCI), gender and in a 5-year age groups ranging from ages of 60’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
114
5
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 37 publications
26
114
5
4
Order By: Relevance
“…Savva et al showed that the TUG (OR 1.57, 95% CI 1.44–1.72) has strong associations with frailty, suggesting that the TUG is a sensitive and specific measure of frailty . Furthermore, Ibrahim et al reported that older adults with MCI took longer to accomplish the TUG . The results of the current study showed significant associations between the TUG and cognitive frailty.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Savva et al showed that the TUG (OR 1.57, 95% CI 1.44–1.72) has strong associations with frailty, suggesting that the TUG is a sensitive and specific measure of frailty . Furthermore, Ibrahim et al reported that older adults with MCI took longer to accomplish the TUG . The results of the current study showed significant associations between the TUG and cognitive frailty.…”
Section: Discussionsupporting
confidence: 60%
“…24 Furthermore, Ibrahim et al reported that older adults with MCI took longer to accomplish the TUG. 25 The results of the current study showed significant associations between the TUG and cognitive frailty.…”
Section: Discussionsupporting
confidence: 51%
“…Recently, TUG has been reported to correlate with cognitive impairment as well as age and gender. 23 Other factors such as education and daily activity levels including exercise, which were not examined in the present study, could have some effects on TUG.…”
Section: Discussionmentioning
confidence: 83%
“…Complex neural processes enable and control walking, but when these processes are disrupted through dementia, the cognitive impairment results in functional deficits, including gait disturbance (Bridenbaugh & Kressig, 2015). Mild cognitive impairment (MCI) has been identified as a transition phase between normal cognitive ageing and early dementia (Ibrahim, Singh, & Shahar, 2017). Reduced mobility is a major concern in older patients with MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced mobility is a major concern in older patients with MCI. Alterations in gait occur due to reduced muscle mass and strength, deterioration of postural stability, vestibular function and impairments of the primary motor cortex (Ibrahim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%